Gas Monetisation Intricacies: Evidence from Indonesia - Hakam, Dzikri Firmansyah; Asekomeh, Ayodele O. (International Journal of Energy Economics and Policy, 2018)
Indonesia’s geographical spread as an archipelago results in a unique and sophisticated electricity distribution. Consequently, PLN, Indonesia’s state-owned electricity company, faces several challenges in implementing a robust gas monetisation scheme given these peculiar features of Indonesia’s electricity sector. We identify and evaluate the risks and critical issues regarding Indonesia’s gas monetisation policy formulation and implementation, particularly the changing regulation and reforms of the past three decades. We surmise that a sound energy policy of gas investment and utilisation by PLN and other energy stakeholders is fundamental. This will manifest in sound business strategies, especially in addressing contractual difficulties and infrastructural deficiencies in securing long-term gas supplies for gas power plants. Some positive approaches are already being adopted by the Indonesian electricity sector stakeholders to tackle the challenges in gas transportation like small scale LNG, marine LNG and CNG but these efforts need to be consistently pursued over the planning horizon. Keywords: gas monetisation; long-term gas supplies; gas transportation JEL Classifications: L95, N7, Q4